Training on Economic Empowerment for Fishermen Community in Ambulu Village, Losari Sub-District, Cirebon Regency, West Java, Indonesia - Sukono Sukono; Riaman Riaman; Soeryana Hasbullah (International Journal of Ethno-Sciences and Education Research, 2021)
The welfare of fishermen in Indonesia is still very low and many of them have not been able to meet their family's daily needs. This is caused by various factors that affect their economic condition. This paper aims to conduct economic empowerment training for fisheries communities in Ambulu Village, Losari District, Cirebon Regency, West Java, Indonesia. In this study, 115 respondents Ambulu village fishermen are included in the study. The reviewed factors include social factors, work system factors, and economic factors themselves in meet the needs of fishermen's family. As much as 79.13% of respondents were able to meet their daily needs, while 20.87% were unable to meet their daily needs. This shows that other efforts are needed from fishermen to fulfil their daily needs in order to improve their welfare.